Automation of Infectious Focus Assay for Determination of Filovirus Titers and Direct Comparison to Plaque and TCID50 Assays - Patrick T. Keiser; Manu Anantpadma; Hilary Staples; Ricardo Carrion; Robert A. Davey (Microorganisms, 2021)
Ongoing efforts to develop effective therapies against filoviruses rely, to different extents, on quantifying the amount of viable virus in samples by plaque, TCID50, and focus assays. Unfortunately, these techniques have inherent variance, and laboratory-specific preferences make direct comparison of data difficult. Additionally, human errors such as operator errors and subjective bias can further compound the differences in outcomes. To overcome these biases, we developed a computer-based automated image-processing method for a focus assay based on the open-source CellProfiler software platform, which enables high-throughput screening of many treatment samples at one time. We compared virus titers calculated using this platform to plaque and TCID50 assays using common stocks of virus for 3 major Filovirus species, Zaire ebolavirus, Sudan ebolavirus, and Marburg marburgvirus with each assay performed by multiple operators on multiple days. We show that plaque assays give comparable findings that differ by less than 3-fold. Focus-forming unit (FFU) and TCID50 assays differ by 10-fold or less from the plaque assays due a higher (FFU) and lower (TCID50) sensitivity. However, reproducibility and accuracy of each assay differs significantly with Neutral Red Agarose Overlay plaque assays and TCID50 with the lowest reproducibility due to subjective analysis and operator error. Both crystal violet methylcellulose overlay plaque assay and focus assays perform best for accuracy and the focus assay performs best for speed and throughput.